Optimization of Intelligent Management System for Crafts Production Based on Internet of Things - Xiaojiang Zhou; Keqi Li (Complexity)
Crafts are a special kind of personalized goods that can be personalized with the help of the Internet to better meet consumers’ individuality and make them part of the personalized craft design. The development of information technology has made it possible to grasp personal information and talk to individuals, and the past practice of grasping consumers’ needs by age level has become obsolete, and providing one-to-one product service to customers through the Internet will become a new market growth point. The design and implementation of the system hardware are introduced by focusing on the functional circuits of various sensors of the data collection terminal, The functional circuit of the wireless communication module CC2530, the functional circuit of the microprocessor STM32, and the functional circuit of the collection terminal. In addition, this paper introduces the development environment of IAR software, the implementation of sensor acquisition function, 4 G module communication function, and coordinator network from the software point of view and provides a detailed explanation using program flowcharts. Next, by comparing the three filtering algorithms, an error optimization algorithm can be used to optimize the filtered data errors and obtain better results. By establishing an experimental platform for collecting all kinds of data, a network formation experiment is performed, and the coordinator normally forms the network, and the collected and processed data by the algorithm are matched to the MATLAB simulation platform. The Topix is compared with the exact data measured by the sensor. Finally, calculations show that two dry batteries can be used to maintain the system over 6 months. The system provides power and low-power design is practical and effective.